Measurement of normal optic nerve for Sudanese pediatric using magnetic resonance imaging - Ahmed, Rihab A. Yousif; Suliman, Awadia G.; Abdullah, Abdulmalek Y.; Mohammed, Alrayah A.; Abdulghani, Amna R.; Aodalkream, Esra N.; Altejany, Namarig A.; Edriss, Yasir M. (International Journal of Research in Medical Sciences, 2020)
Background: Much congenital and intracranial pathology may affect optic nerve (ON) and caused increased or decreased in size, so the measurement is crucial and aiding in diagnosed of some neurogenic and endocrine disorders. The aim of this study was to measure the normal ON length and diameter by magnetic resonance imaging among pediatric at Khartoum state Sudan. Methods: This was descriptive, cross section study, done in 100 Sudanese pediatrics with age from 1 month to 15 years came to Magnetic resonance imaging (MRI) department for MRI brain at three hospitals in Khartoum state (Al-Amal national hospital, Al-Zaitona hospital and Modern Medical Center) during the period from December 2019 to March 2020, all of patients had no pathological or medical condition that may affect the orbits and optic nerve (OON), any child with and medical condition or pathology related to orbits excluded from study sampling. The data were collected by data collection sheet designed especially for this study then analyzed. Results: The study found that the mean diameter of ON was 2.06±0.44 mm, the mean length of right ON was 31.54±4.11 mm, there is no significant different in measurement between males and females (p>0.05), there was strong significant correlation between ON length and diameter with children age (r=0.592**, 0.654**, p<0.001 respectively). Conclusions: The study concluded that there was strong correlation between right and left ON diameter and length with age.